Decoupling mobility and charge carrier concentration in AgR-AgPO3glasses (R = Cl, Br, I) - Rodrigues, Bruno P.; Ebendorff-Heidepriem, Heike; Wondraczek, Lothar (Solid State Ionics, 2019)
Halide-containing silver phosphate glasses have been used as model systems for the study of the ionic conductivity of oxide glasses for the past 50 years, mostly due to the massive increase in conductivity observed as the halide concentration is increased, even if the molar ratio of silver is kept constant. Furthermore there is still no consensus if the increased conductivity is due to an enhancement of the number of effective charge carriers (glass as a weak electrolyte) or a higher charge carrier mobility (glass as a strong electrolyte). In this work we investigate the electrical properties of silver-halide-containing silver metaphosphate glasses through Impedance Spectroscopy. We find the glasses to follow the “canonical scaling”, which coupled with the diffusional nature of the conductivity allows us to show that the number of effective charge carriers remains constant with increasing halide concentration, and that the conductivity follows the same scaling as the ionic mobility.
CRIS-Team Scopus Importer:2023-04-20